Fiber Bragg gratings operating across arbitrary wavelength ranges - Mizuno, Yosuke; Motoishi, Naoki; Noda, Kohei; Theodosiou, Antreas; Kalli, Kyriacos; Lee, Heeyoung; Nakamura, Kentaro; Soto, Marcelo A. (My University, 2023)
We demonstrate that fiber Bragg gratings in polymer optical fibers can lead to reflection peaks in any wavelength range when exciting high-order propagation modes, which can enhance the design of sensing systems for specific applications.
Keywords: fiber Bragg gratings; multimodal interference; optical fiber sensors; strain sensing; vibration sensing